Psychosocial experiences of frontline nurses working in hospital-based settings during the COVID-19 pandemic - A qualitative systematic review - Hongxuan Xu; Sigrid Stjernswärd; Stinne Glasdam (Elsevier, 2021)
Background: Frontline nurses have been directly exposed to the SARS-CoV-2 virus and come in close contact with patients during the COVID-19 pandemic. Nurses execute tasks related to disease control and face multiple psychosocial challenges in their frontline work, potentially affecting their mental well-being and ability to satisfyingly perform their tasks. Objectives: To explore the psychosocial experiences of frontline nurses working in hospital-based settings during the COVID-19 pandemic. Design: The qualitative systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. Registered in PROSPERO (CRD42021259111). Data sources: Literature searches were performed through PubMed, CINAHL, and the WHO COVID-19 database. Inclusion criteria were: All types of nurses having direct contact with or taking care of patients; Primary, secondary, and tertiary health-care services admitting and treating COVID-19 patients; Experiences, perceptions, feelings, views in psychosocial aspects from the identified population group; Qualitative studies; Mixed methods studies; Language in English; Published date 2019-2021. Exclusion criteria were: Commentaries; Reviews; Discussion papers; Quantitative studies; Language other than English; Published in 2018 or earlier; Studies without an ethical approval and ethical statement. Review methods: The studies were screened and selected based on the inclusion and exclusion criteria. Quality appraisal was conducted according to the Critical Appraisal Skills Program qualitative study checklist. Data was extracted from included studies and a thematic synthesis was made. Results: A total of 28 studies were included in the review. The experiences of 1141 nurses from 12 countries were synthesised. Three themes were constructed: 'Nurses' emotional, mental and physical reactions to COVID-19', 'Internally and externally supported coping strategies', and 'A call for future help and support'. Conclusion: Nurses working frontline during the COVID-19 pandemic have experienced psychological, social, and emotional distress in coping with work demands, social relationships, and their personal life. The results pointed to a need for increased psychological and social support for frontline nurses to cope with stress and maintain mental well-being, which may subsequently affect nursing care outcomes.